P207 Thoracic involvement in IgG4-related disease. (12th November 2015) - Anstey, RM; Corcoran, JP; Culver, EL; Talwar, A; Hallifax, RJ; Psallidas, I; Cargill, TN; Manganis, CD; Barnes, E; Rahman, NM
Abstract : Background and objectives: IgG4-related disease (IgG4-RD) is a multi-system fibro-inflammatory disorder originally described in association with autoimmune pancreatitis (AIP), usually but not always in the context of elevated serum IgG4 levels. Thoracic manifestations of IgG4-RD include mediastinal lymphadenopathy, lung nodules or masses, interstitial lung disease, bronchiectasis and pleural disease. The authors' regional IgG4-RD service is one of the largest UK-based units treating patients with this condition. Specialist clinics and multidisciplinary team meetings operate alongside an active research programme. We aimed to describe the frequency with which thoracic abnormalities – either as a symptomatic presenting feature of IgG4-RD or an incidental asymptomatic finding on imaging – were present in a prospectively recruited patient cohort. Method and results: Patients referred to the authors' IgG4-RD service from 2005 onwards and confirmed as having a diagnosis of IgG4-RD were included. Diagnoses were made using established clinical criteria (HISORt for AIP and Japanese International Consensus Diagnostic Criteria for systemic disease); tissue specimens were assessed using the Boston histopathological consensus criteria where available. Patients were followed prospectively; clinicopathological data relating to presentation and clinical progress were stored in a secure database with the consent of participants. In patients without symptomatic thoracic manifestations of IgG4-RD, routine clinical imaging (CXR and CT) was reviewed where available for evidence of incidental asymptomatic disease. 61 IgG4-RD patients with thoracic imaging available were included; mean age at diagnosis was 60.3 years (SD 14.6). 43 (70.5%) patients were male. The majority of patients (85.2%) presented with features of intra-abdominal disease. 6 patients (9.8%) had evidence of symptomatic thoracic disease on the basis of clinical presentation, radiology and/or histology. A further 15 (24.6%) patients had abnormal imaging suggestive of asymptomatic thoracic IgG4-RD. Conclusion: A significant proportion of IgG4-RD patients have evidence of symptomatic and asymptomatic thoracic manifestations of this multi-system disease. Respiratory physicians should consider IgG4-RD in their differential diagnosis for a range of pulmonary presentations, particularly where there is co-existing extra-thoracic organ involvement. Making a diagnosis of IgG4-RD impacts on access to established therapeutic options including corticosteroids and rituximab to which the disease is responsive in the inflammatory phase.